ANALISIS PENERAPAN TAUKIL WALI NIKAH PERSPEKTIF MUHAMMADIYAH DAN NAHDATU ULAMA - Nur, Muhammad Imran; Ridwan, Muh Saleh; Fatimah, Siti Nurul (Universitas Islam Negeri Alauddin Makassar, 2024)
The study, entitled Analysis of the Application of Taukil Guardians of Marriage from the Perspective of Muhammadiyah and Nahdatul Ulama in Pinrang Regency, describes the application of marriage guardian taukil based on the views of Muhammadiyah and Nahdatul Ulama in Pinrang Regency. The marriage guardian taukil is the submission of the marriage guardian in the marriage contract process. The problems in this study are the first, the factors that influence the application of the marriage guardian taukil in Pinrang Regency. The two views of Muhammadiyah and Nahdatul Ulama on Taukil Guardian Marriage in Pinrang Regency. The background of this research is based on the author's interest in the practice of taukil guardians of marriage in Pinrang Regency which is influenced by the views of two major Islamic organizations, namely Muhammadiyah and Nahdatul Ulama. Meanwhile, the author's observations on social phenomena related to the practice of marriage guardian taukil among the public have many question marks from two perspectives between Muhammadiyah and Nahdatul Ulama. The type of research used in this research is qualitative research using a phenomenological approach that examines the object of research in terms of phenomena that occur in the community. Based on the results of the research, the authors describe that there are two factors influencing the application of marriage guardian taukil in Pinrang Regency, namely cultural factors and community knowledge factors. Meanwhile, Muhammadiyah's view on the application of marriage guardian taukil is more inclined to prioritize or prioritize lineage guardians to become guardians in marriage, but if the lineage guardian is absent or unable to do so, other guardians are allowed. The Nahdatul Ulama's view is that it allows anyone who is a guardian in marriage as long as they do not leave the group or party that has been determined in Islamic law. In accordance with the description of the factors and perspectives of Muhammadiyah and Nahdatul Ulama on the application of marriage guardian taukil, it is recommended that the authorized party in this case the Office of Religious Affairs (KUA) can educate the public regarding the application of marriage guardian taukil in Pinrang Regency.